2004
DOI: 10.1108/07363760410549140
|View full text |Cite
|
Sign up to set email alerts
|

Values and lifestyles of individualists and collectivists: a study on Chinese, Japanese, British and US consumers

Abstract: Based on a multinational lifestyle survey, this study investigated consumer lifestyle differences between individualist cultures (Britain and the USA) and collectivist cultures (China and Japan). Congruent with previous findings on values and lifestyles differences between idiocentrics (individualists) and allocentrics (collectivists) at the emic level (USA), this etic-level (crosscultural) study found that consumers in the individualist cultures, compared with those in the collectivist cultures, were more bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(90 citation statements)
references
References 33 publications
6
78
1
3
Order By: Relevance
“…Such acts are not publicly accepted by the mainland Chinese society, yet, 22 these people felt that at the Festival there was less, if any, public criticism, an atmosphere of 'anything goes'. Some Chinese social-cultural context research has highlighted the predominance of a collectivist perspective, a greater level of social influence and conformity to the social norms (Gilbert & Tsao, 2000;Hsu, 1981Hsu, , 1985Lau, 1992;McCullough et al, 1986;Sun et al, 2004). Previous research has also shown that in interdependent cultures, such as China, emphasis is placed on fitting in, behaving in a 'proper' way, and living up to others' expectations (Gao, 1998;Markus & Kitayama, 1991).…”
Section: * Please Insertmentioning
confidence: 99%
See 1 more Smart Citation
“…Such acts are not publicly accepted by the mainland Chinese society, yet, 22 these people felt that at the Festival there was less, if any, public criticism, an atmosphere of 'anything goes'. Some Chinese social-cultural context research has highlighted the predominance of a collectivist perspective, a greater level of social influence and conformity to the social norms (Gilbert & Tsao, 2000;Hsu, 1981Hsu, , 1985Lau, 1992;McCullough et al, 1986;Sun et al, 2004). Previous research has also shown that in interdependent cultures, such as China, emphasis is placed on fitting in, behaving in a 'proper' way, and living up to others' expectations (Gao, 1998;Markus & Kitayama, 1991).…”
Section: * Please Insertmentioning
confidence: 99%
“…These Chinese cultural norms include the predominance of a collectivist (We) perspective rather than 'Western' individualistic (I) motivations; a greater acceptance of inequality; a social dependence and greater level of influence by others and the social environment; a stronger motivation to conform and to maintain a harmonious social order (concern for others); a lesser motivation to pursue freedom and democracy (concern for self) and a generally lower level of satisfaction or happiness with life (Gilbert & Tsao, 2000;Hsu, 1981Hsu, , 1985Lau, 1992;McCullough, Tan, & Wong, 1986;Sun, Horn, & Merritt, 2004). These cultural stereotypes have been challenged in several studies which reveal contradictory findings in that mainland Chinese culture reflects western individualistic perspectives such as pursuit of independence, self-respect, freedom and equality (Feather, 1986;Lau, 1988Lau, , 1992Stipek, Weiner, & Li, 1989).…”
Section: Insert Table 1 Herementioning
confidence: 99%
“…Les quelques recherches empiriques qui ont été effectuées sur ce sujet se fondent sur une diversité de listes de valeurs qu'on peut classer en deux catégories. La première mobilise des listes occidentales, telles que la Rokeach Value Survey (Tai, 2008), la liste de valeurs de Kahle (Kau et Lim, 2005), la Schwartz Value Survey (Ralston et al, 1999;Egri et Ralston, 2004;Chia et al, 2007) et les dimensions culturelles de Hofstede (zhang et Gelb, 1996;Sun et al, 2004) ou de Triandis (Yang, 2004), tandis que la seconde développe des listes de valeurs plus spécifiques pour la Chine, comme la Chinese Value Survey (Chinese Cultural Connection, 1987), le Li et le Yi (Piron, 2006) ou encore la trilogie « confucianisme -bouddhismetaoïsme » (zhang et Jolibert, 2000(zhang et Jolibert, , 2003.…”
Section: Johannes Schaaper Zhen Jiao Kedge Business School Docteur Eunclassified
“…Nos résul-tats montrent clairement que les domaines motivationnels les plus importants pour l'ensemble de nos 1671 répondants sont « la conformité », « la bienveillance » et « la sécurité », dont notamment les valeurs personnelles « sécurité familiale », « honnêteté », « honorant les aînés », « obéissance », Ce positionnement est conforme à celui trouvé par Ralston et al (1997) et Egri et Ralston (2004, qui situent les Chinois sur les dimensions collectivistes, dépassement de soi et conservation. Nous confirmons également les conclusions de zhang et Gelb (1996), qui constatent une tendance collectiviste chez les Chinois, de Ralston et al (1996), qui parlent de la Chine comme étant une société confucéenne et de Ralston (1993) (zhang et Jolibert, 2003;Sun et al, 2004;zhang et al, 2005), notre recherche confirme que les femmes chinoises sont davantage confucéennes, collectivistes et conservatrices que les hommes chinois, qui ont une tendance individualiste plus marquée.…”
Section: Contributions Théoriquesunclassified
“…A convenient sampling technique was used for the collection of data. For measuring the life style and cultural values, scale was adopted from the study of Sun, Horn, and Merritt (2004) and for measuring the impulse buying behavior scale was adopted form the study of (Rook, 1987). For the purpose of collecting the data from amongst many options researcher created an online survey form which was been circulated and been filled by 256 respondents.…”
Section: Methodsmentioning
confidence: 99%